Advanced clinical skills and physical diagnosis - Berg, Dale (Blackwell Science, 1999)
This book presents a step-by-step approach to diagnosis and management of common clinical problems. Topics are organized in head to toe order with each chapter covering the basic examination, advanced examination, and numerous possible diagnoses.